Islamic Educational Values in Poetry as Pedagogical Resources for Character Education - Fatwa (Al-Mudarris, 2025)
This study examines Islamic educational values embedded in poetry and explores their potential as pedagogical resources for character education. While poetry has often been viewed as an expressive literary form, its educational dimension, particularly within the framework of Islamic education, remains underexplored. This research aims to identify and analyze core Islamic educational values reflected in selected poems and to explain how these values can contribute to character formation. Employing a qualitative library research design, the study uses descriptive-analytical methods to examine poetic texts through the lens of Islamic educational theory. Islamic values in this study are conceptualized as principles related to faith, morality, worship, self-discipline, and social responsibility, which are analyzed through thematic interpretation of poetic language and symbolism. The findings indicate that poetry effectively conveys Islamic educational values in an implicit yet meaningful manner, enabling readers to internalize moral and spiritual teachings through aesthetic experience. Poetry functions not only as a literary artifact but also as a pedagogical medium that integrates cognitive, affective, and spiritual dimensions of learning. This study contributes to the discourse on Islamic education by highlighting poetry as an alternative pedagogical resource for character education that remains relevant in contemporary educational contexts.